Altered Functional Connectivity Differences in Salience Network as a Neuromarker of Suicide Risk in Euthymic Bipolar Disorder Patients - Sobczak, Anna Maria; Bohaterewicz, Bartosz; Marek, Tadeusz; Fafrowicz, Magdalena; Dudek, Dominika; Siwek, Marcin; Tereszko, Anna; Krupa, Anna; Bryll, Amira; Chrobak, Adrian Andrzej (Frontiers in Human Neuroscience, 2020)
Objective: The occurrence of death by suicide in patients diagnosed with bipolar disorder is as much as 60 times greater than in the general population Even during the state of euthymia pa-tients are characterized by suicide risk. The aim of the study is to investigate the baseline brain activity in euthymic bipolar disorder patients in regard to suicide risk. We hypothesized that patients compared to healthy control group will demonstrate altered functional connectivity among resting state networks which will be directly related to current suicide risk. Method: 41 subjects were enrolled in the study consisting control group (n=21) and euthymic bipolar disorder patients group (n=20). Functional magnetic resonance imaging was used to evaluate resting state brain activity and ROI-ROI functional connectivity analysis was per-formed. Suicidal risk was estimated using The Suicide Behaviors Questionnaire-Revised Results: A two sample t-test revealed decreased functional connectivity between regions in-volved in the salience network in patients compared to the control group. This decrease was negatively correlated with current suicide risk. Conclusions: Obtained results suggest the association between risk of suicide and activity of regions responsible for functions such as learning from mistakes, prospective thinking and sen-sory integration.